Developing innovative learning media using Wordwall Application to foster teachers’ competency - Hartono, Rudi; Rifani, Salsabila Adrisdityas Candra; Jamilah, Siti; Ozturk, Omer Tayfur (UIN Raden Mas Said Surakarta, 2025)
The integration of technology in education remains a challenge for many teachers, hindering their ability to improve learning quality. According to the 2024 Education Report Card, there was a 3.72% decrease in learning quality compared to 2023, indicating the need for innovative solutions. One potential solution is the Wordwall application, which enables the creation of interactive learning games and activities. This study aims to develop Wordwall-based learning media to enhance teachers' performance and competency in utilizing technology for teaching. The study employs a Research and Development (R&D) methodology, involving stages of needs analysis, design, development, validation, testing, and evaluation. The subjects of the study were elementary school teachers who participated in trials using the developed Wordwall media. Findings show a significant improvement in teachers' competencies, with their understanding and application of technology in teaching increase from 75% to 95%. Additionally, the use of Wordwall application allowed teachers to design more interactive and engaging learning activities, which fostered greater student involvement. The evaluation also revealed that the learning media was easy to use and well-received by teachers. The study concludes that Wordwall application-based learning media effectively supports teachers in enhancing their teaching performance, offering a practical tool for integrating technology into the classroom.